CHARITY CONTENT DEBATE ON SOCIAL MEDIA - Kuni Farikhal Khusna; Safaruddin Al Ihwan; Rifqi Fajar Atha Qolbi; Iqlima Dwi Pangesti; Adinda Titania Salsabila; Sabitha Wahyu Amanda Putri; Dicky Bagus Sambadha; Nur Rofiq (Journal Analytica Islamica, 2024)
Charitable content has become an increasingly widespread phenomenon on social media platforms in recent years. This research aims to investigate the factors contributing to the rising popularity of charitable content and its impact on society. The research method used was online surveys involving participants from various backgrounds. The results of the study indicate that charitable content captures public attention because it has high emotional value and the ability to trigger altruistic behavior. Additionally, social media platforms offer a quick and easy way for individuals to spread messages of goodwill and rally support for social causes. However, there are also negative impacts that need to be considered, such as the potential for misuse or concerns about opportunism. This study underscores the importance of responsible management of charitable content by social media users and other relevant parties to maximize its positive impact on society.